Direct coupling of haloquinolines and sulfonyl chlorides leading to sulfonylated quinolines in water. Issue 3 (17th January 2019) - Bao, Pengli; Wang, Leilei; Liu, Qishun; Yang, Daoshan; Wang, Hua; Zhao, Xiaohui; Yue, Huilan; Wei, Wei
Graphical abstract: Highlights: Coupling reaction of haloquinolines with sulfonyl chlorides in water. Excellent regioselectivity and scale-up synthesis. Base-, extra activator- and organic solvent-free conditions. In situ generated zinc bis-sulphinate as sulfone reagent and activator. Abstract: A simple and efficient method has been developed for construction of sulfonylated quinolines via coupling of haloquinolines and sulfonyl chlorides in water. The present methodology provides an attractive approach to various sulfonylated quinolines in moderate to good yields with favorable functional group tolerance, which has the advantages of operation simplicity, readily available starting materials, excellent regioselectivity, scale-up synthesis, and organic solvent-free conditions.